Crystal structure of catena{(μ2-1,10-phenanthroline-κ4N,N,N′,N′)-(μ2-1,10-phenanthroline-κ3N,N,N′)potassium(I) {[bis(2-hydroxyethyl)iminiumyl](sulfanidyl)methyl}sulfanide hemi(1,10-phenanthroline)}, {C24H16KN4, 0.5(C12H8N2), C5H10NO2S2} - Lo Kong Mun; Lee See Mun; Tiekink Edward R.T. (Zeitschrift für Kristallographie - New Crystal Structures, 2020)
C35H30KN6O2S2, monoclinic, C2/c (no. 15), a = 32.8001(4) Å, b = 7.1562(1) Å, c = 26.0400(3) Å, β = 94.385(1)°, V = 6094.32(13) Å3, Z = 8, Rgt(F) = 0.0315, wRref(F2) = 0.0911, T = 100(2) K.